Electro-Synthetic Optimization of Host Material Based on MIL-100(Fe) - Witri Wahyu Lestari; Joni Hartono; Marisa Adreane; Khoirina Dwi Nugrahaningtyas; Candra Purnawan; Sentot Budi Rahardjo (Molekul, 2016)
Electro-synthesis of Metal-Organic Frameworks types of MIL-100(Fe) (MIL = Material Institute of Lavoisier) in ethanol: water (1: 1) with electrolyte TBATFB 0.1 M has been optimized by varying voltage (12, 13, 14 and 15 Volt) and temperature (room temperature, 40, 60 and 80 °C). The product showed light brown powder which upon activation becomes dark brown. Optimum condition achieved during use voltage of 15 Volts and at a temperature of 40 °C with 33% yield. The obtained material was characterized by XRD and compared to CCDC 640536 simulated patterns to confirm the phase purity of the product. As comparison hydrothermal and reflux method have been carried out. Characterization by FTIR has also undertaken to ensure the coordination between the metal cation (Fe3+) and the BTC ligand (BTC = 1,3,5-Benzene Tri Carboxylate). Meanwhile pore analysis using SAA confirmed that MIL-100(Fe) obtained by electrolysis method has a BET surface area reached till 569.191 m²/g with a total pore volume of 0.4540 cc/g and an average pore diameter reached 16 Å. Based on SEM analysis, morphology material show particle size between 0.4-8.6 μm and has a thermal stability up to 350 °C according thermo-gravimetric analysis. Due to the presence of Lewis acid sites on Fe-trimeric unit, porosity features on MIL-100(Fe) and a fairly high thermal stability, this material is potentially used as the host material for the catalyst in the conversion reactions model for green diesel production.